Correlation of Rainfall Data and Stream Flow - Anuar, Nur shazliena; Ahamad , Noor Ain Sofia; Sahat , Suhaila (Multidisciplinary Applied Research and Innovation, 2022)
A drought is a period of time when a part of the country or region receives less rain than usual. Droughts have a significant negative impact on global social and economic development. In 2014, water rationing was implemented in nearly all Johor districts, including Batu Pahat, Kluang, Mersing, Kota Tinggi, and Kulai Jaya. The aim of this study is to spread more widely that rain is the biggest influence for the drought season. In order to determine rainfall characteristic in Rantau Panjang, Johor and determine water level of Sungai Johor at Rantau Panjang, Johor. The Mann Kendall Test was the main method employed in this study. The Mann Kendall Test is used to look for consistently expanding or diminishing patterns (monotonic) in Y values in data collected over time. It may be a non-parametric test, which suggests it works for all dispersions The result shows there are significant positive relationship between the rainfall and stream flow data, r (12) = 0.41, p > 0.05 (alpha = 0.05) and a significant positive relationship between the rainfall and water level data, r (7) = 0.24, p > 0.05 (alpha = 0.05). In future reseach study it is recommended that more data analysis from more stations will be requested to obtain an overall pattern in Peninsular Malaysia.